The Effect of Return on Equity, Dividend Payout Ratio, and Debt to Asset Ratio on Retail Investor Investment Decisions - Kimsen, Kimsen; Barus, Irwan Irawadi; Purnomo, Djauhar Edi; Malahayati, Rina; Sudarmanto, Eko (Westscience Press, 2025)
This study investigates the influence of Return on Equity (ROE), Dividend Payout Ratio (DPR), and Debt to Asset Ratio (DAR) on the investment decisions of retail investors in Indonesia. Utilizing a quantitative approach, data were collected from 130 retail investors through a structured questionnaire using a Likert scale (1–5). The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3. The results indicate that all three financial indicators—ROE, DPR, and DAR—have a significant positive effect on investment decisions. ROE and DPR are positively perceived by investors as indicators of profitability and income stability. Interestingly, DAR also shows a positive influence, suggesting that investors may view moderate leverage as a sign of strategic growth. The model demonstrates strong explanatory power with an R² value of 0.749, highlighting that financial performance indicators are critical determinants of investment behavior among retail investors. The findings provide valuable implications for corporate financial managers, investors, and regulators aiming to enhance transparency and investor confidence in capital markets.